Biological treatment of a contaminated gaseous emission from a paint and varnish plant—from laboratory studies to pilot-scale operation - Bastos, Filipe S.C. (2011)
A Vapour-Phase Bioreactor (VPB), namely a biotrickling filter, was scaled-up and operated in-situ for the treatment of gaseous emissions from a paint and varnish industrial plant. A microbial culture able to degrade the target compounds was enriched and a laboratory-scale VPB was established in order to evaluate the treatment's performance. The VPB presented removal efficiencies higher than 90% when exposed to Organic Loads (OL) of ca 50 g h−1 m−3 of reactor. The VPB was exposed to dynamic conditions often found in-situ (eg night and weekend shutdown periods) and showed a fast capacity to recover, with and without mineral medium recirculation. After a prolonged interruption period (10 months), the VPB was not able to cope with OL of ca 25 g h−1 m−3 of reactor and re-inoculation was required in order to recover the treatment performance. The VPB also showed limited treatment when exposed to higher OL (ca 500 g h−1 m−3 of reactor). The VPB was then scaled-up and a 3 m3 VPB was operated in-situ, showing removal efficiencies higher than 50% when exposed to an OL of c 5 g h−1 m−3 of reactor, thus complying with current legal demands. The addition of a maintenance feed was shown to be a useful tool for VPB pilot-scale operation when shutdown periods occurred. A factorial design of experiments was carried out, which allowed reduction to one-tenth of the initial supply of the main mineral medium constituents, namely phosphate buffer, ammonium and magnesium salts, and also elimination of the metal supplement. Overall, the VPBs were shown to be robust equipment, being able to respond actively to dynamic treatment scenarios, particularly night and weekend shutdown periods. Copyright © 2003 Society of Chemical Industry